The Geological Evolution of the Variscan Jebilet Massif, Morocco, Inferred From New Structural and Geochronological Analyses. Issue 12 (10th December 2018) - Delchini, S.; Lahfid, A.; Lacroix, B.; Baudin, T.; Hoepffner, C.; Guerrot, C.; Lach, P.; Saddiqi, O.; Ramboz, C.
Abstract: The present work aims at understanding the tectonic evolution of the Jebilet massif, Morocco, during the Late Paleozoic as constrained by structural, metamorphic, and geochronological studies. From Late Devonian to Early Carboniferous, bordering faults controlled the opening of the Jebilet intracontinental basin (D0 stage) as shown by sedimentary infill. This episode was accompanied by a magmatic activity, newly dated between 358 ± 7 Ma and 336 ± 4 Ma. The first record of the Variscan event affected the Jebilet by the Late Visean‐Namurian and is represented by allochthonous superficial nappes emplaced at shallow depth in a moderately lithified sedimentary succession. D1 also developed regional‐scale recumbent folds trending E‐W that may suggest N‐S crustal shortening not generating crustal thickening nor contributing to metamorphism. The main Variscan D2 episode consists of a progressive evolution from bulk coaxial deformation to noncoaxial dextral transpression consistent with NW‐SE horizontal shortening, resulting in a moderate thickening. This episode was accompanied by HT‐LP metamorphism and syntectonic intrusions controlled by an inherited thermal anomaly in relation with the intracontinental rifting stage (D0 ). Based on previous age determinations from syntectonic leucogranite and metamorphic rocks, D2 is dated between 310 and 280 Ma. The tectono‐metamorphic evolution of the Jebilet massif can be correlated with a plate‐tectonic scenario evolving from, first a Late Devonian‐Early Carboniferous basin formation during stretching of the north‐Gondwana margin and initiation of the Paleotethys Ocean, and, second, to a Late Carboniferous‐Early Permian ocean closure (Rheic or Paleotethys Oceans depending of scenarios) that resulted in the final Variscan‐Alleghanian tectonics. Key Points: Extension and magmatism during latest Devonian to Early Carboniferous (D0 ) are related to opening of the Paleotethys Ocean Late Carboniferous to Early Permian Variscan tectonics (D1, D2 ) developed HT‐LP metamorphism that cannot be explained by crustal thickening Moderate crustal thickening and HT‐LP metamorphism can be explained by an inherited thermally weakened crustal domain